Appearance of the bladder on initial voiding cystogram in boys with PUV and its relation to pre and postnatal findings - Pecorelli, S.; Ferdynus, C.; Delmas, J.; Harper, L. (Frontiers in Pediatrics, 2024)
Bladder profile in boys with Posterior Urethral Valves can be very varied with a spectrum going from high pressure, unstable, hypocompliant small bladders to hypercompliant, large acontractile bladders, with some being near-normal. Our question was whether appearance, specifically of the bladder, on initial VCUG was correlated to prenatal features and whether it could predict early postnatal outcome. Patients and Method We used a prospectively gathered database of boys with prenatally suspected PUV. We analyzed whether the appearance, specifically of the bladder, was related to date of prenatal diagnosis, presence of a megacystis on prenatal ultrasound, presence of vesico-ureteral reflux (VUR), presence of abnormal DMSA scan, nadir creatinine or presence of febrile urinary tract infection (fUTI) during the first two years of life. Results The database comprised 90 cystograms. 15% of bladders were judged normal/regular, 54 % were small/diverticular and 31% were large/diverticular. Bladder appearance was not associated with presence of prenatal megacystis, abnormal DMSA scan, VUR, nor rate of fUTI. The only significant associations were normal/regular bladder and early prenatal diagnosis (p=0.04) and normal/regular bladder and elevated nadir creatinine (>75µmol/l) (p=0.01). Conclusion In conclusion, we believe that when focusing solely on the appearance of the bladder, excluding information about the urethra and presence of reflux, the cystogram alone is insufficient to inform on future bladder function. This could be used as an argument in favor of performing early urodynamics in this population.